Efektifitas POC Sabut Kelapa Dalam Nutrisi Hidroponik Pada Pertumbuhan dan Hasil Tanaman Sawi Pakcoy (Brassica Rapa L.) - Miftakhurrohmat, A; Abror, M; Arifin, Saiful (Savana Cendana, 2024)
This study aims to determine the effectiveness of coco coir POC in hydroponic nutrition on the growth and yield of mustard greens (Brassica rapa L.) This research was conducted in October 2022 - February 2023, using a single factor randomized block design and repeated 6 times with the following treatments (i) P1 = Without POC + AB Mix Nutrition 100%; (ii) P2 = 25% POC + 75% AB Mix Nutrients; (iii) P3 = 50% POC + 50% AB Mix Nutrition; (iv) P4 = 75% POC + 25% AB Mix Nutrients; (v) P5 = 100% POC + 25% AB Mix Nutrients. The observed variables consisted of plant height, root length, leaf area, fresh weight, dry weight and harvest index. The data were analyzed using analysis of variance (ANOVA) then followed by the Honest Significant Difference tukey test at the 5% level. The results of the riset showed a very real response at the age of 21, 28 and 35 HST on the observation of plant height variables, as well as on the wet weight and dry weight variables and the harvest index. However, it showed no significant response to observing root length and leaf area.